Hadith #4553 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; al-Qasim bin Salam القاسم بن سلام; Muhammad bin 'Abdullah bin Qahzad محمد بن عبد الله بن قهزاد; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Sa'id bin Abi Sa'id; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Zayd ibn Thabit (Sunan Abi Dawud)
The bloodwit for what resembled intentional murder should be forty pregnant she-camels in their fifth year, thirty she-camels in their fourth year, and thirty she-camels in their third year. The bloodwit for unintentional murder is thirty she-camels in their fourth year, thirty she-camels in their third year, and twenty she-camels in their second year.
Grade: Da'if